Development of weighting factor for LCIA [Life Cycle Impact Assessment] based on conjoint analysis - Itsubo, N. (National Inst. of Advanced Industrial Science and Technology Tsukuba, Ibaraki (Japan)); Sakagami, M; Kuriyama, K; Washida, T; Kokubu, K; Inaba, A (ENVIRONMENTAL SCIENCE, 2003)
Weighting, final step of LCIA, is attractive to provide single index. Many of weighting methodologies have already been proposed until now. Among them, economic valuation has been taken attention because of the facility to understand and availability. Conjoint analysis, one of the methodologies seen as economic methodology, is attractive tool to compare between the significance of attributes. In environmental economics, conjoint analysis is considered as effective and the most up-to-date method internationally. Endpoint type LCIA methodology based on Japanese environmental conditions is now being developed in LCA national project of Japan. One of the characteristics of this methodology is that we can calculate the potential damages of safeguard subjects considering the knowledge of environmental science. Damage assessment enables us to minimize the numbers of attributes. In order to provide weighting factors to practitioners whose goals of LCIA are to obtain single index, we applied conjoint analysis to weight across safeguard subjects. The purpose of this research is to measure WTP (Willingness To Pay) for each safeguard subjects and to establish weighting factors of them. The elements we chose are: human health, social welfare, primary productivity, biodiversity, and tax rate. The main research was conducted in Tokyo. The statistical result shows that all of the coefficients are statistically significant. This research belongs to LCA National Project of Japan.